ANALISIS YURIDIS TERHADAP PENDIRIAN PERMUKIMAN DI PESISIR PANTAI KOTA SIBOLGA (Studi di Kelurahan Pancuran Bambu Kecamatan Sibolga Sambas Kota Sibolga) - sinabariba, rinaldi; zaidar; kaban, maria (Magister Hukum Universitas HKBP Nommensen, 2022)
Houses as a support for community livelihoods in water areas and places for the development of life are very much needed by people who live in water areas, so that people in the Sibolga Cityarea build houses on the coast and coastal borders. The research was conducted using legalresearch, namely normative juridical and empirical juridical, descriptive analytical research isresearch that aims to describe a situation or symptom or to determine whether there is arelationship between a symptom and other symptoms. Data collection techniques used areliterature studies and field studies in the form of data collection and interviews with the Head ofthe Housing, Settlement and Environmental Office of Sibolga City. The results of the researchand discussion show that the regulation of the use of coastal areas for community settlements inSibolga City is regulated in Law Number 1 of 2011 concerning Housing and Settlement Areas,Presidential Regulation Number 51 of 2016 concerning Coastal Boundaries and Sibolga MayorRegulation Number 16 of 2018 Regarding the Utilization of Coastal Areas and Coastal Borders inSibolga City. The legal status of control of coastal waters for residential areas in Sibolga City canbe granted for residential housing if based on Article 5 paragraph (2) of the Minister of ATR/BPNNumber 17 of 2016 is a land right according to Article 16 of the BAL. However, when viewed fromthe presence of houses built on water, not on land (land). The earth's surface referred to in theLoGA is land which includes the surface of the earth on land and also the surface of the earthunder water, including sea water. So, in this case the floating house can be given land rights. Theappropriate right to be given to the floating house is the right to use the land. The policy ofgranting land rights to coastal areas in Sibolga City is only to give use rights to fishermen wholive in the border of the orphanage and not property rights.